2019
DOI: 10.31223/osf.io/43ydf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accelerating numerical wave-propagation using wavefield adapted meshes, Part I: Forward and adjoint modelling

Abstract: An order of magnitude speed-up in finite-element modelling of wave propagation can be achieved by adapting the mesh to the anticipated space-dependent complexity and smoothness of the waves. This can be achieved by designing the mesh not only to respect the local wavelengths, but also the propagation direction of the waves depending on the source location, hence by anisotropic adaptive mesh refinement. Discrete gradients with respect to material properties as needed in full waveform inversion can still be comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This however changed when the azimuthal smoothness of a global wavefield was discovered by Leng et al (2016), which naturally gave rise to a spectral-element pseudo-spectral method AxiSEM3D (Leng et al 2016(Leng et al , 2019 adapted to wavefield complexity: As the wavefield is sparsely represented on a Fourier basis, it leads to a drastic speedup in computational cost. Building on Leng et al's idea on azimuthal smoothness, this has also been identified by van Driel et al (2019), who showed that the discrete adjoint approach can obtain exact 2D Fréchet kernels at a much lower computational cost. They achieved such adaptability by an alternative implementation of exploiting azimuthal smoothness by azimuthally adaptive meshing instead of Fourier series, thereby retaining the conventional 3D SEM solver strategy at the expense of having to mesh in 3D.…”
Section: Introductionmentioning
confidence: 89%
“…This however changed when the azimuthal smoothness of a global wavefield was discovered by Leng et al (2016), which naturally gave rise to a spectral-element pseudo-spectral method AxiSEM3D (Leng et al 2016(Leng et al , 2019 adapted to wavefield complexity: As the wavefield is sparsely represented on a Fourier basis, it leads to a drastic speedup in computational cost. Building on Leng et al's idea on azimuthal smoothness, this has also been identified by van Driel et al (2019), who showed that the discrete adjoint approach can obtain exact 2D Fréchet kernels at a much lower computational cost. They achieved such adaptability by an alternative implementation of exploiting azimuthal smoothness by azimuthally adaptive meshing instead of Fourier series, thereby retaining the conventional 3D SEM solver strategy at the expense of having to mesh in 3D.…”
Section: Introductionmentioning
confidence: 89%
“…Similarly, data storage of models, kernels, waveforms etc., necessary to solve the forward and inverse problems, push the limits of modern clusters, while complexity scales as tomography implements larger domains, higher resolutions, and increased data. Nevertheless, the trade-offs of full-waveform methods are attractive given the physical accuracy they provide, and much of the current research in the field is focused on optimizing the forward and inverse problems through novel approaches such as wavefield adapted meshes (Thrastarson et al, 2020), or dynamic batching (van Driel et al, 2020;van Herwaarden et al, 2020).…”
Section: Full-waveform Tomographymentioning
confidence: 99%